NILAI-NILAI PENDIDIKAN KARAKTER DALAM CERPEN LENTERA PADAM KARYA FAISAL FAJRI - Mike, 123Dian; Ummah, Nurul Afidatul (Hasta Wiyata, 2024)
This research aims to describe the values of character education contained in the short story Lentera Padam by Faisal Fajri. The research was designed with a qualitative approach. Data was collected using the reading and note-taking method and analyzed qualitatively descriptively. The results of the research show that there are five values of character education including (1) religious, namely Tera's exemplary attitude which always prays for goodness from the Almighty (2) hard work, this is done by Tera who always works hard to earn a living to meet her living needs ( 3) affection, as brothers and sisters who have become alone. (4) creative, this character is played by Tera's sister. He has a younger sibling who is very creative (5) appreciates achievements, this behavior is carried out by Tera, he really appreciates his younger sibling's achievements. Tera tries to always attend every competition that her younger sibling participates in, she feels that she is a substitute mother figure for her little sibling.